A critical role for glycine transporters in hyperexcitability disorders - Harvey, Robert J.; Carta, Eloisa; Pearce, Brian R.; Chung, Seo-Kyung; Supplisson, Stéphane; Rees, Mark I.; Harvey, Kirsten (Frontiers in Molecular Neuroscience, 2008)
Defects in mammalian glycinergic neurotransmission result in a complex motor disorder characterized by neonatal hypertonia and an exaggerated startle reflex, known as hyperekplexia (OMIM 149400). This affects newborn children and is characterized by noise or touch-induced seizures that result in muscle stiffness and breath-holding episodes. Although rare, this disorder can have serious consequences, including brain damage and/or sudden infant death. The primary cause of hyperekplexia is missense and non-sense mutations in the glycine receptor (<abbrev>GlyR</abbrev>) α1 subunit gene (GLRA1) on chromosome 5q33.1, although we have also discovered rare mutations in the genes encoding the <abbrev>GlyR</abbrev> β subunit (<abbrev>GLRB</abbrev>) and the <abbrev>GlyR</abbrev> clustering proteins gephyrin (GPNH) and collybistin (ARHGEF9). Recent studies of the Na+/Cl−-dependent glycine transporters <abbrev>GlyT1</abbrev> and <abbrev>GlyT2</abbrev> using mouse knockout models and human genetics have revealed that mutations in <abbrev>GlyT2</abbrev> are a second major cause of hyperekplexia, while the phenotype of the <abbrev>GlyT1</abbrev> knockout mouse resembles a devastating neurological disorder known as glycine encephalopathy (OMIM 605899). These findings highlight the importance of these transporters in regulating the levels of synaptic glycine.